The landscape of Helicobacter pylori-mediated DNA breaks links bacterial genotoxicity to its oncogenic potential - Hadas Sibony-Benyamini; Rose Jbara; Tania Shubash Napso; Layan Abu-Rahmoun; Daniel Vizenblit; Michal Easton-Mor; Shira Perez; Alexander Brandis; Tamar Leshem; Avi Peretz; Yaakov Maman (Genome Medicine)
Abstract Background Helicobacter pylori (H. pylori) infection is a significant risk factor for gastric cancer (GC) development. A growing body of evidence suggests a causal link between infection with H. pylori and increased DNA breakage in the host cells. While several mechanisms have been proposed for this damage, their relative impact on the overall bacterial genotoxicity is unknown. Moreover, the link between the formation of DNA damage following infection and the emergence of cancerous structural variants (SV) in the genome of infected cells remained unexplored. Methods We constructed a high-resolution map of genomic H. pylori-induced recurrent break sites using the END-seq method on AGS human gastric cells before and after infection. We next applied END-seq to cycling and arrested cells to identify the role of DNA replication on break formation. Recurrent H. pylori-mediated break sites were further characterized by analyzing published RNA-seq, DRIP-seq, and GRO-seq data at these sites. γH2AX staining and comet assay were used for DNA breakage quantification. Liquid chromatography-mass spectrometry (LC–MS) assay was used to quantify cellular concentrations of dNTPs. Results Our data indicated that sites of recurrent H. pylori-mediated DNA breaks are ubiquitous across cell types, localized at replication-related fragile sites, and their breakage is dependent on replication. Consistent with that, we found that H. pylori inflicts nucleotide depletion, and that rescuing the cellular nucleotide pool largely reduced H. pylori-induced DNA breaks. Intriguingly, we found that this genotoxic mechanism operates independently of H. pylori cag pathogenicity island (CagPAI) that encodes for the bacterial type 4 secretion system (T4SS), and its virulence factor, CagA, which was previously implicated in increasing DNA damage by downregulating the DNA damage response. Finally, we show that sites of recurrent H. pylori-mediated breaks coincide with chromosomal deletions observed in patients with intestinal-type GC and that this link potentially elucidates the persistent transcriptional alterations observed in cancer driver genes. Conclusions Our findings indicate that dNTP depletion by H. pylori is a key component of its genotoxicity and suggest a link between H. pylori genotoxicity and its oncogenic potential.